The United States and the Privatization of Celestial Bodies under the Outer Space Treaty 1967 - Pasaribu, Desi; Simatupang, Helga Yohana (Contemporary Society and Politics Journal, 2023)
Every country has an equal right to conduct space exploration, both in the development of science and technology and in the utilization of space resources for the survival needs on Earth. Space is the most challenging region to reach as it requires significant time and costs for exploration. This research aims to assist in the regulation of the 1967 Outer Space Treaty regarding the United States’ efforts to explore and privatize planets and moons. The research uses a qualitative descriptive method based on applicable international laws and treaty articles. The findings indicate that the United States has launched policies supporting the development of private space industries, yet there are legal considerations to be addressed, including the Outer Space Treaty, applicable in the context of privatizing planets and moons. The efforts made by the United States in privatizing planets and moons, in line with the 1967 Outer Space Treaty, raise various legal, ethical, and policy questions. The treaty defines international laws governing the use of outer space, including planets and moons.